Association of CXCR4 mRNA Expression with Clinicopathological Aspects of Invasive Breast Carcinoma - Novan Adi Setyawan; Didik Setyo Heriyanto; Naomi Yoshuantari; Irianiwati Irianiwati (Faculty of Medicine Universitas Sebelas Maret, 2021)
ABSTRACT BackgroundBreast cancer is the most common malignancy in women of which majority histological type is Invasive (Ductal) Carcinoma of No Special Type (NST). The prognosis in breast carcinoma is influenced by many factors such as age, tumor size, degree of histology, and lymph node metastasis. Another factor in the development and metastasis of breast cancer is the chemokine receptor CXCR4 and its ligand, CXCL12. Studies state that the expression of CXCR4 in Breast Invasive Carcinoma associated with clinicopathologic aspects remain unclear. This study aims to determine differences in the level of CXCR4 mRNA expression between clinicopathologic aspects in breast carcinoma..MethodA total of 50 samples of formalin-fixed paraffin-embedded (FFPE) tissues diagnosed as invasive breast carcinoma (NST) are used in this study. Samples are divided into groups, namely with and without lymph node metastasis, age <45 years and> 45 years, small and large size, low grade and high grade. CXCR4 mRNA expression is quantitatively examined by qRT-PCR. CXCR4 mRNA expression differences between various clinicopathologic aspects were analyzed by One-Way ANOVAResultOf the 50 samples, 26 samples (52%) revealed increased expression of CXCR4 mRNA compared to normal tissue. There were no significant differences in mRNA expression of CXCR4 between various prognostic factors (p> 0.05) such as the status of lymph node metastasis, histologic grading, size, and age. However, the expression of CXCR4 mRNA is increased in breast carcinoma when compared to normal breast tissue. Nonetheless the level of CXCR4 expression alone is not associated to clinicopathologic aspects in invasive breast carcinoma.ConclusionCXCR4 mRNA expression did not differ significantly between the various clinicopathological aspects of invasive breast carcinoma. Keyword: invasive breast carcinoma, mRNA of CXCR4, Clinicopathologic aspects